Aspekte van luistervaardigheid in gemeenskapsonderrig - Van Niekerk, A. (University of the Free State, 2000)
It has been said that it is the province of knowledge to speak, and the province of wisdom to listen. This statement emphasises the importance of the ability to listen effectively in any communicative encounter, but it does not clarify why the ability to listen is of utmost importance in the communication process. The article sets out by way of argumentation to address the following critical issues: What factors influence listening behaviour? Who is a skilful listener? What is the profile of an effective listener in an academic environment?
Keywords: Effective listening; Communication